Stability of Syk protein and mRNA in human peripheral blood basophils - MacGlashan, Donald (J Leukoc Biol, 2016)
In human basophils, Syk expression is 10-fold lower than most other types of leukocytes. There are indirect studies that suggest that Syk protein is highly unstable (a calculated half-life less than 15 min) in human peripheral blood basophils. Therefore, in these studies, Syk stability was directly examined. Purified basophils were metabolically labeled and a pulse–chase experimental design showed Syk protein to be stable in the time frame of 12 h (95% likelihood that half-life is more than 12 h). However, its synthetic rate was very slow (∼10-fold slower) compared with CD34-derived basophils, which have been shown to express levels of Syk consistent with other mature circulating leukocytes. Syk mRNA expression was found to be 5–30-fold lower than other cell types (CD34-derived basophils, peripheral blood eosinophils, and plasmacytoid dendritic cells). Syk protein and mRNA levels, across cell types, were relatively concordant. Syk mRNA in basophils showed a half-life of 3.5 h, which was greater than that of interleukin-4 or Fc epsilon receptor I-α mRNA (∼2 h), but somewhat shorter than Fc epsilon receptor I-β mRNA (8 h). A comparison of miR expression between CD34-derived and peripheral blood basophils demonstrated only 1 significant increase, in miR-150 (77-fold). Transfection in human embryonic kidney cells of a stabilized form of miR-150 showed that it modified expression of c-Myb mRNA but not of Syk mRNA or protein. These results suggest that low Syk expression in basophils results, not from protein instability and perhaps not from mRNA stability. Instead, the results point to the transcriptional nature of an important point of regulation.